Early Interventions for the Prevention of Posttraumatic Stress Symptoms in Survivors of Critical Illness: A Qualitative Systematic Review. Issue 8 (August 2018) - Roberts, Michael B.; Glaspey, Lindsey J.; Mazzarelli, Anthony; Jones, Christopher W.; Kilgannon, Hope J.; Trzeciak, Stephen; Roberts, Brian W.
Abstract : Objectives: Posttraumatic stress disorder among survivors of critical illness is of public health importance, as it is common and reduces patient quality of life. The objective of this systematic review was to collate the world's literature on interventions aimed at preventing posttraumatic stress disorder among survivors of critical illness. Data Sources: We performed a search of CENTRAL, MEDLINE, EMBASE, CINAHL, and clinical trials registry platforms, with no restriction to language using a comprehensive strategy. Study Selection: Study inclusion criteria were as follows: 1) adult human subjects, 2) patients treated in an ICU setting, 3) intervention arm aimed at reducing posttraumatic stress disorder symptoms, 4) use of a control arm, and 5) an outcome measure assessing development of acute stress or posttraumatic stress disorder symptoms. Data Extraction: We performed a qualitative analysis to collate and summarize effects of identified interventions according to the recommended methodology from the Cochrane Handbook. Data Synthesis: Seventeen studies met all inclusion and no exclusion criteria. There was heterogeneity in interventions and outcome measures used. All studies had some concern for risk of bias as per the Cochrane tool for assessing risk of bias. In eight of 12 studies (67%) testing early interventions (i.e., initiated in the ICU course) and one of five studies (20%) testing delayed interventions following ICU discharge, posttraumatic stress disorder symptoms were decreased among the intervention group compared with controls. Conclusions: Despite a paucity of high-quality clinical investigations, the preponderance of evidence to date suggests that 1) posttraumatic stress disorder among survivors of critical illness may be preventable and 2) early interventions may be the most effective. Abstract : Supplemental Digital Content is available in the text.